Pemberdayaan Masyarakat Terhadap Pengendalian Penyakit Tidak Menular Dukungan Corporate Social Responsibility (CSR) di Kecamatan Cicurug, Kabupaten Sukabumi: Studi Agen Perubahan - Rustika Rustika; Sariah Sariah (Jurnal Persada Husada Indonesia, 2020)
Number of hypertension cases in Cicurug, West Java, Health Center of Sukabumi District is 40% reported risk factors which are smoking habit, and clean healthy living behavior (PHBS) amounted 70%. Non communicable diseases control effort which is done by agent of change (AoC) through community empowerment. These activities could be held in collaboration with Corporate Social Responsibility (CSR). Operational research to analyze the implementation of CSR in community empowerment. Community empowerment is conducted in Nyangkowek Village (As Intervention Village) and Purwasari Village (As Control Village), Cicurug District, Sukabumi Regency. It has been selected 20 AoC from each village. Data were collected by in-depth interviews and observations. The AoC triggered has improved the knowledge, attitude and behavior of AoC in the control of NCD, they became promoters in controlling NCD risk factors for themselves, families, and community. Community empowerment through the selection of candidates and triggering AoC is the key to the successful implementation of P2TMBM. AoC as the spearhead in changing the risky behavior of NCD in the community that is coronary heart, hypertension, and obesity. CSR program in Cicurug District is able to develop community empowerment in controlling NCD risk factors. Health Office and Puskesmas are expected to be facilitators in forming AoC. Assistance by CSR is needed in the effort to control smoking behavior, diet and physical activity.